Head and Neck Paragangliomas in the Czech Republic: Management at the Otorhinolaryngology Department - Guha, Anasuya; Chovanec, Martin (Diagnostics (Basel, Switzerland), 2021)
Head and neck paragangliomas (HNPGLs) are rare neuroendocrine tumors, comprising only 3% of all head and neck tumors. Early diagnosis forms an integral part of the management of these tumors. The two main aims of any treatment approach are long-term tumor control and minimal cranial nerve morbidity. The scope of this article is to present our case series of HNPGLs to stress most important clinical aspects of their presentation as well as critical issues of their complex management. Thirty patients with suspected HNPGLs were referred to our otorhinolaryngology clinic for surgical consultation between 2016-2020. We assessed the demographical pattern, clinicoradiological correlation, as well as type and outcome of treatment. A total of 42 non-secretory tumors were diagnosed-16.7% were incidental findings and 97% patients had benign tumors. Six patients had multiple tumors. Jugular paragangliomas were the most commonly treated tumors. Tumor control was achieved in nearly 96% of operated patients with minimal cranial nerve morbidity. Surgery is curative in most cases and should be considered as frontline treatment modality in experienced hands for younger patients, hereditary and secretory tumors. Cranial nerve dysfunction associated with tumor encasement is a negative prognostic factor for both surgery and radiotherapy. Multifocal tumors and metastasis are difficult to treat, even with early detection using genetic analysis. Detecting malignancy in HNPGLs is challenging due to the lack of histomorphological criteria; therefore, limited lymph node dissection should be considered, even in the absence of clinical and radiological signs of metastasis in carotid body, vagal, and jugular paragangliomas.
Keywords: cranial nerve dysfunction; incidentaloma; otorhinolaryngology; Fisch’s classification; facial nerve palsy; HNPGLs; jugular paragangliomas; Shamblin’s classification